Diet, microbiota, and dysbiosis: a ‘recipe’ for colorectal cancer - Vipperla, Kishore (Food Funct, 2016)
The food we consume feeds not only us, but also a vast and diverse community of microbiota within our gastrointestinal tract. In a process of symbiotic co-evolution, the gut microbiota became essential for the maintenance of the health and integrity of our colon. The advent of next-generation DNA sequencing technology and metabolic profiling have, in the recent years, revealed the remarkable complexity of microbial diversity and function, and that the microbiota produce a wide variety of bioactive products that are not only active at the mucosal surface, but also absorbed and circulated throughout the body, influencing distant organ health and function. As a result, several microbiota compositional patterns and their associations with both health and disease states have been identified. Importantly, a disturbed micro-biota–host relationship, termed dysbiosis, is now recognized to be the root cause for a growing list of diseases, including colorectal cancer (CRC). There is mounting in vitro and in vivo evidence to suggest that diet selects for the microbiota composition and several health promoting and deleterious effects of diet are, in fact, mediated by the microbiota. Recent findings of the feasibility of dietary fiber to boost the colonic microbial synthesis of anti-proliferative and counter carcinogenic metabolites, particularly butyrate, underscores the prerequisite of dietary modification as a key measure to curb the pandemic of CRC in westernized countries. Better understanding of the diet–microbiota interplay and large-scale studies to evaluate the efficacy of dietary modification and gut microbiota modulation in reversing dysbiosis and restoring health could offer novel preventative and/or therapeutic strategies against westernized diseases, which are now considered the chief threat to public health.